Model Penentuan Kualitas Getah Karet Menggunakan Metode Multi Attributive Border Approximation Area Comparison (Mabac) - Anriani, Ayu; Astuti, Indah F.; Agus, Fahrul (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The rubber plant is classified as a plantation crop that is cultivated for the production of latex. Theprimary objective of farming rubber plants is the production of latex. To enhance the productivity andcaliber of latex, it is essential to engage in the cultivation of rubber plants and employ appropriateprocessing techniques. PT. Multi Kusuma Cemerlang is the sole rubber manufacturing facility situated inthe Palaran District of Samarinda City, East Kalimantan. The current operational procedure employed bythe factory for assessing rubber quality relies on a manual system. This approach possesses inherentrisks since it is susceptible to errors, which can result in material losses for the company. This study aims todevelop a model for evaluating the quality of latex at PT—Multi Kusuma Cemerlang, employing the MultiAttributiveBorder Approximation Area Comparison (MABAC) approach. The implementation of thisapproach is utilized in the development of online applications for decision support systems. Theassessment of latex quality involves the evaluation of eight distinct data criteria, which encompass color,texture, form, contamination, water content, shelf life, storage location, and clumping. The findings of thestudy indicate that the MABAC approach is capable of offering optimal suggestions in terms of rubberquality. In one of the test data sets utilized for assessing the quality of rubber, the model generated thedecision for the rubber identified as code 20230223#10, exhibiting a probability value of 0,168488496.